1975
DOI: 10.1111/j.1365-2125.1975.tb00475.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in drug metabolism with increasing age: 2. phenytoin clearance and protein binding.

Abstract: 1 Comparison of phenytoin clearance showed a marked increase in people over 65 years of age compared with people under 45 years of age. 2 This difference was apparent if phenytoin was given orally or intravenously. 3 Phenytoin clearance correlated inversely with phenytoin binding and plasma albumin, both of which were found to be reduced in the elderly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
44
1

Year Published

1976
1976
1998
1998

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(49 citation statements)
references
References 11 publications
(8 reference statements)
4
44
1
Order By: Relevance
“…An inverse relationship between serum clearance and plasma protein binding has been described for phenytoin (Hayes, Langman & Short, 1975). It is also (Jordan, Shillingford & Steed, 1976;Patsalos & Lascelles, 1977) and preliminary work suggests that a reciprocal effect of phenytoin on the plasma protein binding of valproic acid may take place in vitro (Monks, personal communication).…”
Section: Discussionmentioning
confidence: 91%
“…An inverse relationship between serum clearance and plasma protein binding has been described for phenytoin (Hayes, Langman & Short, 1975). It is also (Jordan, Shillingford & Steed, 1976;Patsalos & Lascelles, 1977) and preliminary work suggests that a reciprocal effect of phenytoin on the plasma protein binding of valproic acid may take place in vitro (Monks, personal communication).…”
Section: Discussionmentioning
confidence: 91%
“…However, the change in the volume of distribution and slightly higher clearance may reflect alterations in protein binding. It has been shown that plasma concentrations of albumin decrease with age (Woodford-Williams et al, 1964) leading to changes in free drug fraction and consequently to changes in clearance and volume of distribution (Greenblatt et al, 1980 (Triggs & Nation, 1975;Hayes et al, 1975;Bach et al, 1981).…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacokinetic studies in the elderly have been performed using intravenous administration with only a few drugs including antipyrine (O'Malley etal., 1971) phenytoin (Hayes, Langman & Short, 1975) diazepam (Klotz et al, 1975), chlordiazepoxide (Roberts et al, 1978), propranolol (Castleden & George, 1979), chlormethiazole and lignocaine (Triggs, 1979).…”
Section: Discussionmentioning
confidence: 99%